Inertia of parasite infection versus host biomass fluctuation. Issue 2 (February 2023) - de Montaudouin, Xavier; Stout, Leslie
Graphical abstract: Highlights: Cockle biomass was monitored for 15 years as a second intermediate host of trematodes. Parasite abundance in cockles is correlated to cockle biomass with an 8 year time-lag. Parasite/host systems can sustain a durable second intermediate host deficit. Abstract: Infection by parasites with complex life cycles such as trematodes depends on many environmental factors which may result in a time-lag between host biomass fluctuations and parasite density in hosts. A cockle (marine bivalve, second intermediate host) population and its associated parasite community were monitored over 15 years. A time-shift correlation analysis suggests that trematode abundance in cockles responds to cockle biomass after a long delay (8 year time-lag). Thus, these parasites can sustainably support a deficit of their intermediate host.